2018
DOI: 10.1159/000487347
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Mechanical Stretch Induced Smooth Muscle Cell Changes in Cerebral Aneurysm Progress by Reducing Collagen Type IV and Collagen Type VI Levels

Abstract: Background/Aims: Cerebral aneurysm growth is characterized by continuous structural weakness of local smooth muscle cells, though the mechanism is unclear. In this study, we examine protein changes in cerebral aneurysm and human brain vascular smooth muscle cells after cyclic mechanical stretch. We further explore the relationship between the smooth muscle cell changes and reductions in the levels of collagen types IV and VI. Methods: Saccular cerebral aneurysms (n=10) were collected, and temporal artery sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
4
18
0
Order By: Relevance
“…Among these 180 proteins, 88 were significantly up‐regulated, and 92 were down‐regulated in the IA group compared to the STA group. The results were shown in our previous studies 16,17 …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Among these 180 proteins, 88 were significantly up‐regulated, and 92 were down‐regulated in the IA group compared to the STA group. The results were shown in our previous studies 16,17 …”
Section: Resultssupporting
confidence: 82%
“…Collagen type IV, another essential protein present in SMCs that can stimulate the α‐SMA and SM‐MHC promoters, 42 has been previously verified by us to be crucial in focal adhesion and ECM pathways. We found that human IA tissues had fewer SMCs and less collagen type IV 16 . We also found that CAV‐1 is a ubiquitous gene that appears in almost every study of the rabbit aneurysm model.…”
Section: Discussionsupporting
confidence: 54%
“…Degeneration of the ECM is primarily induced by secretion of inflammatory cytokines and cell infiltration 19 21 . Our previous comparative proteomic analysis demonstrated that collagen IV and VI levels were reduced in comparisons of aneurysm and STA tissues 22 . In this study, we observed that levels of collagen IV and VI were clearly decreased in the aneurysm wall by IHC.…”
Section: Discussionmentioning
confidence: 96%
“…Several inflammatory mediators are triggered and then release large amounts of inflammatory cytokines and oxidative factors. This can cause a number of pathological processes including disruption of internal elastic laminate, vascular smooth muscle cell (VSMC) phenotype modulation, and dysfunctional extracellular matrix (ECM) remodeling [24]. When vessel walls degenerate, intracranial arteries become too weak to resist the blood dynamic force, and pouch-like dilatations of cerebral arteries occur.…”
Section: Introductionmentioning
confidence: 99%